Classical Painting of Wayang Kamasan to be UNESCO Intangible Cultural Heritage - Ni Made Ariani (Bali Tourism Journal, 2022)
In the past, Balinese artists have been perfecting their skills in arts as an expression of gratitude to the Higher being or as a service to the community. One of the classic painting styles that endured through time in Bali since the days when King Anak Wungsu reigned. The classic art is the painting style from Kamasan village, Klungkung, known as Lukisan Wayang Kamasan or Kamasan Shadow Puppet Painting. Kamasan puppet painting is an expression of Wayang performance, composed into a 2-dimensional painting. The method of storytelling in the form of painting developed rapidly during the reign of ancient Bali, especially by the people who lived in the Kamasan village of ??Klungkung. The steps in determining the layout of the image, the drawing process, color making, and the coloring process of the Kamasan puppet painting are still used traditionally. The Indonesia Education and Culture ministry announced the submission of the Wayang Kamasan painting to UNESCO in early February 2022. This submission is a re-submission after the Kamasan puppet painting was proposed as an Intangible Cultural Heritage in 2018 by the Indonesian Government. However, the submission of the Kamasan Wayang painting as an intangible cultural heritage in 2018 was rejected because the documents were incomplete. The purpose of the protection in this convention is for art preservation, especially, for future generations. It means that anyone can use it, not just the group to whom the recognition of ownership of the intangible cultural heritage is given.